Penyelesaian Pembagian Hak Cipta Dan Hak Atas Merek Sebagai Harta Bersama Dalam Perceraian Islam - Titie Rachmiati Poetri (Lex Renaissance, 2020)
Assets generated in marriage are referred as joint assets or marital assets. Joint assets can be in the form of tangible or intangible objects. By using a descriptive method and a statutory approach, this normative legal research aims to analyze the following problems: first, do the copyright and trademark rights generated in a marriage qualify as joint assets according to Islamic law of marriage? Second, how to resolve the distribution of copyright and trademark rights as joint assets in divorce based on Sharia? The results of the research conclude that first, copyright and trademark rights as intangible objects become joint assets if the rights are generated in marriage, even though they are only registered in the name of either husband or wife. Second, in the event of a divorce, the copyright royalty and the right to the mark may become the object of shared joint assets, in which the royalty will be divided by two or based on the considerations of the roles and responsibilities of husband and wife during marriage.